Analisis Penegakan Hukum Pada Tindak Pidana Penipuan - Apriyanti Rukmana, Lusi; Rahaditya, R. (Dinasti Review Publisher, 2024)
This research aims to explain the condition that law is very important and is the main pillar in describing a country. In upholding just laws in an institution, people are needed who have integrity and have good commitment and can serve the country. Furthermore, this research aims to explain law enforcement regarding the problems of criminal acts of fraud that occur in society. This study employed a normative approach as its methodology. This normative research method examines several documents, including statutory regulations, judicial rulings, legal theory, and expert opinions. This study will use books, literature, journals, periodicals, and expert opinions as data collection methods. The findings of the analysis from this study demonstrate that crimes in the form of criminal acts of fraud can be prevented or at least lessened by law enforcement officials using various legal sanctions in accordance with their jurisdiction.